2018
DOI: 10.1111/1462-2920.14360
|View full text |Cite
|
Sign up to set email alerts
|

SuhB, a small non‐coding RNA involved in catabolite repression of tetralin degradation genes in Sphingopyxis granuli strain TFA

Abstract: Global dRNA-seq analysis of transcription start sites combined with in silico annotation using Infernal software revealed the expression of 91 putative non-coding sRNA in Sphingopyxis granuli TFA cells grown on different carbon sources. Excluding housekeeping sRNAs, only one additional sRNA, which belongs to the Rfam SuhB family (RF00519), was detected by Infernal but with an incorrect size according to the experimental results. SuhB is highly conserved across the Sphingopyxis genus. Expression data revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Although nepR genes are not usually automatically annotated due to their small size, the TFA genome revealed that it contains two short orfs that could actually code for NepR-like proteins and were therefore designated as nepR1 (SGRAN_0992) and nepR2 (SGRAN_1162). The one designated nepR2 is located upstream ecfG1, shares the same transcription start site (TSS) 21 and actually overlaps with ecfG1 by 4 bp (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nepR genes are not usually automatically annotated due to their small size, the TFA genome revealed that it contains two short orfs that could actually code for NepR-like proteins and were therefore designated as nepR1 (SGRAN_0992) and nepR2 (SGRAN_1162). The one designated nepR2 is located upstream ecfG1, shares the same transcription start site (TSS) 21 and actually overlaps with ecfG1 by 4 bp (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to know the specific contribution of EcfG1 and EcfG2 to the transcription of different GSR promoters, in vitro transcription assays were performed with either EcfG1 or EcfG2 forms of the RNAP using five putative promoter regions, representatives of the most frequent -10 boxes, as templates. In order to restrict the regulatory inputs to the effect of the σ factor alone, the DNA regions used as templates would only extend from the putative TSS 21 to the -35 sequence. Among the chosen templates, nepR2 and gsp (general stress protein, SGRAN_0888) were selected for having a consensus CGTT -10 box, but also for differing in the -35 element (they present a GGAAC and a GCAAC -35 box, respectively, the two most frequent in the GSR-dependent promoters, see Supp.…”
Section: Figurementioning
confidence: 99%
“…In addition, beyond providing more accurate predictions, GEMs provide useful computational workflows for the incorporation of -omics data within biological networks 31 . We thus included available transcriptomic data for strain TFA grown aerobically with tetralin and 3-HB 32 in an attempt to optimize iIG743 predictions for the strain grown on each of the two carbon sources. To do this, we reduced the solution space of iIG743 by using the GIMME method 33 .…”
Section: Qualitative and Quantitative Of Iig743 Validationmentioning
confidence: 99%
“…C-1 isolated from an eutrophic lake in China has been shown to harbor the ability of MCs degradation [9]. Sphingopyxis fribergensis Kp5.2, originally isolated from soils, was reported to degrade styrene [14]. In addition, Sphingopyxis granuli TFA isolated from the Rhine river was able to grow in organic solvent tetralin [15].…”
Section: Introductionmentioning
confidence: 99%